Look at the picture.
Use the Pythagorean theorem:
![b^2=a^2+a^2\\\\b^2=2a^2\to b=\sqrt{2a^2}\\\\b=\sqrt{a^2}\cdot\sqrt2\\\\b=a\sqrt2](https://tex.z-dn.net/?f=b%5E2%3Da%5E2%2Ba%5E2%5C%5C%5C%5Cb%5E2%3D2a%5E2%5Cto%20b%3D%5Csqrt%7B2a%5E2%7D%5C%5C%5C%5Cb%3D%5Csqrt%7Ba%5E2%7D%5Ccdot%5Csqrt2%5C%5C%5C%5Cb%3Da%5Csqrt2)
![\sin\theta=\dfrac{opposite}{hypotenuse}\\\\\theta=45^o,\ opposite=a,\ hypotenuse=a\sqrt2](https://tex.z-dn.net/?f=%20%5Csin%5Ctheta%3D%5Cdfrac%7Bopposite%7D%7Bhypotenuse%7D%5C%5C%5C%5C%5Ctheta%3D45%5Eo%2C%5C%20opposite%3Da%2C%5C%20hypotenuse%3Da%5Csqrt2%20)
substitute
![\sin45^o=\dfrac{a}{a\sqrt2}=\dfrac{1}{\sqrt2}\cdot\dfrac{\sqrt2}{\sqrt2}=\dfrac{\sqrt2}{2}](https://tex.z-dn.net/?f=%5Csin45%5Eo%3D%5Cdfrac%7Ba%7D%7Ba%5Csqrt2%7D%3D%5Cdfrac%7B1%7D%7B%5Csqrt2%7D%5Ccdot%5Cdfrac%7B%5Csqrt2%7D%7B%5Csqrt2%7D%3D%5Cdfrac%7B%5Csqrt2%7D%7B2%7D)
Answer: ![\sin45^o=\dfrac{\sqrt2}{2}](https://tex.z-dn.net/?f=%5Csin45%5Eo%3D%5Cdfrac%7B%5Csqrt2%7D%7B2%7D)
Answer:
<h2>
y = -4/9</h2>
Step-by-step explanation:
Given the system of equations y = 3/2 x − 6, y = −9/2 x + 21, since both expressions are functions of y, we will equate both of them to find the variable x;
3/2 x − 6 = −9/2 x + 21,
Cross multiplying;
3(2x+21) = -9(2x-6)
6x+63 = -18x+54
collecting the like terms;
6x+18x = 54-63
24x = -9
x = -9/24
x = -3/8
To get the value of y, we will substitute x = -3/8 into any of the given equation. Using the first equation;
y = 3/2x-6
y = 3/{2(-3/8)-6}
y = 3/{(-3/4-6)}
y = 3/{(-3-24)/4}
y = 3/(-27/4)
y = 3 * -4/27
y = -4/9
Hence, the value of y is -4/9
Answer: y= x-2
Step-by-step explanation:
Perpendicularity entails the slope of line a is -1 divided by the slope of line b
m1= (-1/m2)
From y=Mx +c
We compare with x-4y=7
y=(1/4)x-7/4
Meaning m2= 1/4
m1= -1/(1/4)= -1*4= -4
((y-y1)/(x-x1))= ((y2-y1)/(x2-x1))=m1
x1= 2, y1= -4
((y-(-4))/(x-2))= -4
((y+4)/(x-2))= -4
Cross multiply
y+4= -4(x-2)
y= x-2
The answer to -16^-3/4 is -8